2020
DOI: 10.1111/ntwe.12161
|View full text |Cite
|
Sign up to set email alerts
|

Technologies in caregiving: professionals’ strategies for engaging with new technology

Abstract: This article explores the adoption of new technology in organisations that provide senior citizen care. Inspired by Niklas Luhmann’s systems theory, we study how technology reduces complexity by identifying client needs and ensuring predictability in service delivery. However, how technologies are adopted in practice is not determined by technology since it is also structured by care‐workers' continuous decision‐making. Against this backdrop, we explore how technologies alter the conditions for decision‐making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“… 11 , 22 , 35 Then again, the standardization of work also simplifies the complexity of patients’ needs, improves work routines and enhances the quality of health care services. 9 , 36 , 37 Hence, the outcomes of incorporating ICT into health care organizations appear not to be related to the technology itself but to the choices and processes involved when integrating ICT into health care professionals’ clinical work. 38 …”
Section: Discussionmentioning
confidence: 99%
“… 11 , 22 , 35 Then again, the standardization of work also simplifies the complexity of patients’ needs, improves work routines and enhances the quality of health care services. 9 , 36 , 37 Hence, the outcomes of incorporating ICT into health care organizations appear not to be related to the technology itself but to the choices and processes involved when integrating ICT into health care professionals’ clinical work. 38 …”
Section: Discussionmentioning
confidence: 99%
“…To document and analyze technology appropriation in an organization with a continuous improvement (CI) program in place, we conducted an in-depth case study [41][42][43][44] on how care workers appropriated a personal digital assistant (PDA) in a nursing home. Previously, empirical studies have shown that deployments of the PDA for its intended functionalities-that is to remotely register and retrieve resident data-range from great successes to utter failures [16,31,37,[45][46][47][48][49][50]. The few studies explicitly elaborating PDA appropriation underline that care workers appropriate the PDA covertly, regarding both the intended [16,31] and the unintended functionalities [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…velfaerdsteknologiske implementeringer herunder telemedicin, telehealth og telehomecare (se fx Sorknaes, 2013;Lunde, Drachmann & Christiansen, 2017;Højlund & Villadsen, 2020;Pols, 2012;, Harrison, Koppel & Bar-Lev, 2007Andersen & Hindhede, 2018). Teknologierne har i dag overtaget og forandret opgaverne for både de professionelle og borgerne.…”
Section: Hjemmeplejens Digitale Virkelighedskløftunclassified